2021
DOI: 10.1111/1742-6723.13727
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the modifiable areal unit problem in assessing determinants of emergency department demand

Abstract: Objective To examine the impact of the modifiable areal unit problem (MAUP) in an investigation of factors associated with ED demand in Perth, Western Australia, in 2016. Furthermore, to advocate a means of avoiding this impact. Methods ED presentations were classified as: urgent medical, non‐urgent medical, urgent trauma or non‐urgent trauma. In each group, sex‐stratified, age‐adjusted multivariate associations with socio‐economic status and distance to the nearest ED and general practitioner (GP) were estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…This aligns with the findings in Fontanet et al [14] where the smallest level failed to provide meaningful inference due to smaller populations and counts. Kok et al [9] also found this to be the case when analysing hospitalisation rates for foot-related issues among the Indigenous population of Australia. Our findings, in conjunction with theirs, suggest that while aiming for the highest level of resolution may be optimal to reduce the biases of the MAUP, using mesh blocks can introduce other problems such as small numbers, zero populations, and computational inefficiencies.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…This aligns with the findings in Fontanet et al [14] where the smallest level failed to provide meaningful inference due to smaller populations and counts. Kok et al [9] also found this to be the case when analysing hospitalisation rates for foot-related issues among the Indigenous population of Australia. Our findings, in conjunction with theirs, suggest that while aiming for the highest level of resolution may be optimal to reduce the biases of the MAUP, using mesh blocks can introduce other problems such as small numbers, zero populations, and computational inefficiencies.…”
Section: Discussionmentioning
confidence: 82%
“…One proposed method to minimising the MAUP is through using high spatial resolution [9]. However, we found that meshblocks, which typically represent 30 to 60 dwellings [28], were too sparse for a condition as rare as cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This bias results in different trends learned when the data are aggregated at different spatial scales. For example, when designing an AI system for ambulance demand, only estimates based on minimal-resolution data should be relied upon, as ambulance demand using areal data is potentially misleading owing to the modifiable areal unit problem [ 117 ].…”
Section: Introductionmentioning
confidence: 99%